Patterns of richness and endemism of the Mexican herpetofauna, a matter of spatial scale?. (5th December 2013) - Ochoa‐Ochoa, Leticia M.; Campbell, Jonathan A.; Flores‐Villela, Oscar A.
<x xml:space="preserve">Abstract</x> The goal of this study was to compare the richness and endemism patterns of Mexican species of amphibians and reptiles at different spatial scales. We used the best available dataset of distributional ranges generated from ecological niche models and employed geographically weighted regressions (GWRs) to test whether richness and endemism were related. Patterns were found to vary with the scale used for richness and endemism, and these patterns were not coincident. The results showed that: (1) only relatively coarse spatial scales can address latitudinal patterns in amphibians and reptiles, and, in fine scales, they are related to topographic formations; (2) areas of greatest endemism for amphibians and reptiles are located in the highlands of the central or southern part of the country, although not necessarily in the same specific highlands for both groups; (3) there is a strong average correlation between richness and endemism for both groups, indicating that the same factors contribute to both patterns, but these factors act differentially in terms of regions among amphibians and reptiles; and (4) the scale at which the analysis is conducted is important, and we believe that careful consideration of spatial scale must be undertaken to avoid false conclusions. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 305–316.